Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/nature12115
|View full text |Cite|
|
Sign up to set email alerts
|

Sema3A regulates bone-mass accrual through sensory innervations

Abstract: Semaphorin 3A (Sema3A) is a diffusible axonal chemorepellent that has an important role in axon guidance. Previous studies have demonstrated that Sema3a(-/-) mice have multiple developmental defects due to abnormal neuronal innervations. Here we show in mice that Sema3A is abundantly expressed in bone, and cell-based assays showed that Sema3A affected osteoblast differentiation in a cell-autonomous fashion. Accordingly, Sema3a(-/-) mice had a low bone mass due to decreased bone formation. However, osteoblast-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
332
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 340 publications
(349 citation statements)
references
References 36 publications
11
332
4
2
Order By: Relevance
“…This evolutionarily primitive neuron functions bidirectionally-its distal axon terminal not only transduces and transmits pain, but it also releases electrical and paracrine chemical signals that maintain tissue homeostasis. C-fiber trophic signals are critical for the integrity of skin and bone for instance [1,2]. Other C-fiber paracrine secretions modulate tissue responses to injury or threat.…”
Section: Introductionmentioning
confidence: 99%
“…This evolutionarily primitive neuron functions bidirectionally-its distal axon terminal not only transduces and transmits pain, but it also releases electrical and paracrine chemical signals that maintain tissue homeostasis. C-fiber trophic signals are critical for the integrity of skin and bone for instance [1,2]. Other C-fiber paracrine secretions modulate tissue responses to injury or threat.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic blocks were trimmed and 4 or 7-lm thick sections were prepared with a RM2255 (Leica Microsystems). Undecalcified sections of the lumbar vertebrae were stained for von Kossa, Toluidine Blue and TRAP staining, as previously described [6]. Static and dynamic histomorphometric analyses were performed using OsteoMeasure Analysis System (OsteoMetrics) following nomenclature defined by the American Society for Bone and Mineral Research.…”
Section: Histological and Histomorphometric Analysesmentioning
confidence: 99%
“…Very recently, we showed that the sensory nerve plays a core role in bone remodeling [6]. Vascularization supplies various tissues including bone with oxygen, nutrients, hormones and cytokines, suggesting that angiogenesis is vital to the skeletal development and bone remodeling [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that neural and vascular regulation factors, such as semaphorins and netrins, orchestrate bone metabolism. We have demonstrated that semaphorin 3A, which is a diffusible axonal chemorepellent that has an important role in axon guidance, regulates bone remodeling indirectly by modulating sensory nerve development and also found that it enhances the elongation of dendrite in osteocytes (4,5). Semaphorin 3A exerts an osteoprotective effect by both suppressing bone resorption and increasing bone formation (6).…”
mentioning
confidence: 99%